Development of the teacher’s technological pedagogical content knowledge (TPACK) from the Lesson Study: A systematic review - Jiménez Sierra, Ángel Alfonso; Ortega Iglesias, Jorge Mario; Cabero-Almenara, Julio; Palacios-Rodríguez, Antonio (Frontiers in Education, 2023)
A systematic review is presented with the purpose of exploring the trends associated with the development of technological pedagogical content knowledge (TPACK) from Lesson Study. In the 21st century, technology established a complex and necessary relationship with different sectors of society, enabling different conceptual and practical models for the incorporation of technologies in teaching. TPACK was one of the most outstanding. In this perspective, a systematic literature review is presented taking into account 16 studies published between 2015 and 2021 with the purpose of analyzing the development of TPACK in teachers, in research that uses the Lesson Study (LS) as an intervention strategy. The review was carried out in April 2022 using the following databases: Scopus, Web of Science, Spinger Link, Proquest Central, Science Direct, Redalyc, Dialnet and Scielo. The phases of identification, screening, selection and inclusion of the flowchart of the PRISMA guide were applied. The results reveal that the LS constitutes a theoretical and practical framework that provides contextualized opportunities to work on the training needs and interests of teachers, promoting self-assessment and the construction of new conceptions about teaching with technologies. Therefore, the theoretical discussion reveals that the integrative vision of TPACK is the perspective that predominates the development of this type of research.